MANAJEMEN PEMBIYAAN PENDIDIKAN DI SEKOLAH DASAR - Arjunaini Arjunaini; Dahliawati Dahliawati; Yuni Revita; Hadiyanto Hadiyanto; Yahya Yahya (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
A school needs education funding in the form of education funds needed by the school. The factors that influence the education fund itself in a school are teachers, the percentage of students, and the use of education funding itself. The problems that occur in education financing are financial management in schools that are not well managed, besides that there are indications of misappropriation in finances committed by related persons, as well as a lack of school supplies, only coming from students. Funding for education in schools has not been maximized because direct cost and indirect cost sources of funds have not been used optimally. Apart from that, problems that often arise, namely in recording school financial administration and expenses to financial reporting. Current problems with the difficulty of life make the world of education only experienced by the wealthy. The study used in the writing of this article is to use the literature study method where the source comes from books, in Googlei Scholeir or in the form of previous articles and relevant articles related to the problem.